Association of pulmonary hypertension with outcomes in patients with Systemic sclerosis and other connective tissue disorders: review and meta-analysis: PH associated survival in patients with CTDs - Gegenava, Maka; Gegenava, Tea (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Pulmonary hypertension (PH) is a frequent complication of connective tissue disorders (CTDs), with a major impact on the prognosis of the disease. The aim of our study was to perform a systemic review and meta-analysis of published literature evaluating survival function in patients with systemic sclerosis (SSc) with and without PH and to compare survival function between patients with SSc, systemic lupus erythematosus (SLE), other CTDs, and conditions associated with PH. Methods: The established protocol of the Cochrane Collaboration Steps and meta-analysis of observational studies in epidemiology recommendations (MOOSE) were used. Results: 7 studies, including 1470 SSc-PH patients and 1368 SSc patients without PH, and 4 studies, including 108 SLE-PH patients and 1288 SLE patients without PH, assessed survival function were selected. Six studies (including 777 SSc, 249 SLE, 90 idiopathic pulmonary arterial hypertension (IPAH) and 29 primary Sjogren’s syndrome patients) comparing survival function in different subgroups of patients with confirmed PH were included. SSc patients with PH showed the worst survival as compared to SSc patients without PH [OR (95% CI) 3.70 (2.42–5.67); p<0.00001]. The same pattern was observed in patients with SLE. SSc patients with PH were characterized by lower survival function compared to other reasons for PH, including SLE [OR (95% CI) 2.76 (1.95–3.91); p<0.00001]. Conclusions: Patients with SSc-PH are characterized by significantly lower survival function as compared to SSc patients without PH. Among the different entities of PH, SSc shows the worst survival, underlining prognostic significance of detection and evaluation of PH according to the currently established approach.